The Influence of Market Orientation, Product Innovation, and Halal Supply Chain on the Marketing Performance of Muslim MSMEs in Tangerang - Rahmat Krisandi; Fina Fitratun Amaliyah; Efi Syarifudin; Hadi Peristiwo; Sulaiman Jazuli (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2024)
This study aims to analyze the influence of market orientation, product innovation, and halal supply chain on marketing performance among Muslim MSMEs in Pasir Gintung Village, Tangerang Regency, Banten. The research method used is quantitative, with surveys as the data collection technique. The results of multiple linear regression analysis show that these three variables have a positive and significant influence on marketing performance. Market orientation helps understand consumer needs, product innovation creates added value, and a halal supply chain increases consumer trust among Muslims. These findings highlight the importance of enhancing market orientation, product innovation, and halal supply chain management to achieve better marketing performance for Muslim MSMEs in Tangerang.Keywords: Market orientation, Product innovation, Halal supply chain. Marketing performance of Muslim MSMEs